Carbonated steel slag artificial aggregate with self-repairing function and preparation method thereof
By using carbonated steel slag artificial aggregate composed of core particles, transition layer and shell, the problem of existing self-repair materials being easily damaged during concrete mixing is solved, and the function of effectively repairing cracks in concrete is realized. At the same time, solid scrap steel slag is used to capture CO2, which has a simple process and low-carbon technology.
Patent Information
- Application Number
- CN202510009611.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-14
AI Technical Summary
Existing self-repairing materials are prone to damage when concrete is agitated, cost is high and easily deactivated, making it difficult to effectively repair concrete cracks.
Artificial aggregate of carbonated steel slag including core particles, transition layer and shell is used, the core particles are composed of carbonated calcium hydroxide, and the shell layer is composed of carbonated steel slag. Through multiple granulation and accelerated carbonation treatment, the mass ratio of calcium hydroxide and steel slag in the transition layer is regulated to ensure that the degree of carbonation of the core particles is not more than 20%.
The single-particle splitting strength of artificial aggregate of carbonated steel slag is 4~6MPa, ensuring that it is not easy to break during concrete mixing, and effectively releases the repair substance calcium hydroxide when the concrete cracks, repairs cracks, and uses solid waste steel slag to capture CO2, which has a simple process and low-carbon technology.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a carbonated composite artificial aggregate with a self-repairing function and a preparation method thereof. Background Art
[0002] Concrete is the largest building material and is widely used. However, various shrinkages in the cement hydration and hardening process in concrete cause cracks in the concrete. When water, air and harmful ions enter the concrete through the cracks, they can cause steel corrosion, thereby destroying the concrete structure and shortening the service life of the concrete. How to repair concrete cracks is a hot topic in this field.
[0003] At present, cracks are usually repaired in the following ways: 1. Pre-embed hollow capsules or glass fibers containing repair resin or inorganic repair substances. When cracks form and damage the glass tube, the resin or inorganic repair substances overflow to repair the cracks; 2. Pre-add microorganisms and nutrients when mixing concrete. When cracks form, water and air enter the cracks to activate the microorganisms, and the microorganisms produce calcium carbonate precipitation to repair the cracks. However, in the first method, the repair material is easily destroyed during concrete mixing and does not work. In the second method, the microorganisms are expensive and easily inactivated. Summary of the invention
[0004] In view of the technical problems existing in the background technology, the present application provides a carbonated composite artificial aggregate with self-repairing function and a preparation method thereof, aiming to solve the technical problems that the existing self-repairing materials are easily damaged during concrete mixing, are costly and easily deactivated.
[0005] In a first aspect, an embodiment of the present application provides a carbonated steel slag artificial aggregate with a self-repairing function, which includes, from the inside to the outside, a core particle, a plurality of transition layers, and a shell layer, wherein the core particle is composed of carbonated calcium hydroxide, the shell layer is composed of carbonated steel slag, and the plurality of transition layers are provided with at least two layers, and the mass ratio of calcium hydroxide to steel slag gradually decreases from the inside to the outside; The carbonation degree of calcium hydroxide in the inner core particles is not more than 20%, and the splitting strength of the carbonated steel slag artificial aggregate with self-repairing function is 4~6MPa.
[0006] In some embodiments, the mass ratio of calcium hydroxide to steel slag in the transition layer close to the core particles is (4~2):1, and the mass ratio of calcium hydroxide to steel slag in the transition layer close to the shell layer is 1:(4~2).
[0007] In a second aspect, the present application provides a method for preparing a carbonated steel slag artificial aggregate with a self-repairing function, comprising the following steps: S1, mixing calcium hydroxide powder with water and granulating once to obtain core particles; S2, mixing the core particles, calcium hydroxide and steel slag, performing secondary granulation, coating the surface of the core particles with a transition layer, and obtaining a first intermediate product; S3, repeating step S2, and gradually reducing the mass ratio of calcium hydroxide and steel slag in step S2, coating the surface of the core particles with multiple transition layers, and obtaining a second intermediate product; S4, mixing the second intermediate product, steel slag and water, and performing tertiary granulation, coating the surface of the second intermediate product with a shell layer, to obtain a third intermediate product; S5. subjecting the third intermediate product to accelerated carbonation curing to obtain carbonated steel slag artificial aggregate.
[0008] In some embodiments, the carbonation degree of calcium hydroxide powder in the inner core particles of the carbonated steel slag artificial aggregate is no more than 20%, and the splitting strength of the carbonated steel slag artificial aggregate is 4-6 MPa.
[0009] In some embodiments, the conditions for accelerating carbonation are: CO2 volume concentration of 20-99%, pressure of 0.1-0.3 MPa, and time of 8-24 h.
[0010] In some embodiments, the water-to-solid ratio of the inner core particles is 0.45-0.55.
[0011] In some embodiments, the water-to-solid ratio of the shell is 0.10-0.20.
[0012] In some embodiments, the calcium hydroxide powder has a particle size of less than 200 mesh.
[0013] In some embodiments, the slag has a particle size of less than 200 mesh.
[0014] In some embodiments, the diameter of the core particles is 1 / 3 to 1 / 2 of the diameter of the carbonated steel slag artificial aggregate.
[0015] A third aspect is the use of a carbonated steel slag artificial aggregate with self-repairing function in concrete.
[0016] Different from the existing technical solutions, the beneficial effects of this application include: 1. This application makes the single particle splitting strength of carbonated steel slag artificial aggregate 4~6MPa by regulating the initial structure of the first transition layer, the second transition layer and the shell layer and accelerating the carbonation reaction conditions. The main purpose is to make the strength of carbonated steel slag artificial aggregate neither too low nor too high. When it is too low, the carbonated steel slag artificial aggregate is very easy to break during the concrete mixing process; when it is too high, the internal repair substance cannot be released after the concrete cracks. When the strength of carbonated steel slag artificial aggregate is moderate, it is not easy to break during the concrete mixing process, and when the concrete cracks, the aggregate will also crack and release the repair substance calcium hydroxide.
[0017] 2. The present application regulates the water-to-solid ratio of the internal calcium hydroxide powder so that the outer steel slag of the aggregate undergoes carbonation reaction during accelerated carbonation curing, while the internal calcium hydroxide powder has a lower degree of carbonation, which is beneficial to the release of calcium hydroxide, an effective repair substance, when cracks are formed. The released calcium hydroxide can be naturally carbonized in the cracks, and the formed reaction products repair the cracks. In addition, in order to reduce the large performance difference between the carbonated calcium hydroxide in the inner core particles and the carbonated steel slag in the shell, multiple transition layer treatments are used to gradually reduce the gradient. The results of the examples show that the degree of carbonation of the internal calcium hydroxide powder of the carbonated composite artificial aggregate prepared by the preparation method provided in the present application is no more than 20%, and the splitting strength of a single-particle aggregate is 4~6MPa.
[0018] 3. In addition, the preparation method of the carbonated product provided by the present invention has a simple process, utilizes solid waste, captures CO2, has a short maintenance cycle, and is a typical low-carbon technology.
[0019] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. DETAILED DESCRIPTION
[0020] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above description and any variations thereof are intended to cover non-exclusive inclusions.
[0022] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0023] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0024] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0025] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0026] At present, cracks are usually repaired in the following ways: 1. Pre-embed hollow capsules or glass fibers containing repair resin or inorganic repair substances. When cracks form and damage the glass tube, the resin or inorganic repair substances overflow to repair the cracks; 2. Pre-add microorganisms and nutrients when mixing concrete. When cracks form, water and air enter the cracks to activate the microorganisms, and the microorganisms produce calcium carbonate precipitation to repair the cracks. However, in the first method, the repair material is easily destroyed during concrete mixing and does not work. In the second method, the microorganisms are expensive and easily inactivated.
[0027] In order to solve the technical problems that existing self-repairing materials are easily damaged during concrete mixing, have high costs and are easily deactivated, the present application provides a carbonated composite artificial aggregate with self-repairing function and a preparation method thereof, wherein the artificial aggregate prepared by the method has the function of self-repairing concrete cracks, while utilizing solid waste steel slag and capturing CO2.
[0028] In a first aspect, an embodiment of the present application provides a carbonated steel slag artificial aggregate with a self-repairing function, which includes, from the inside to the outside, a core particle, a plurality of transition layers, and a shell layer, wherein the core particle is composed of carbonated calcium hydroxide, the shell layer is composed of carbonated steel slag, and the plurality of transition layers are provided with at least two layers, and the mass ratio of calcium hydroxide to steel slag gradually decreases from the inside to the outside; The carbonation degree of calcium hydroxide in the inner core particles is not more than 20%, and the splitting strength of the carbonated steel slag artificial aggregate with self-repairing function is 4~6MPa.
[0029] In some embodiments, the mass ratio of calcium hydroxide to steel slag in the transition layer close to the core particles is (4~2):1, and the mass ratio of calcium hydroxide to steel slag in the transition layer close to the shell layer is 1:(4~2).
[0030] In a second aspect, the present application provides a method for preparing a carbonated steel slag artificial aggregate with a self-repairing function, comprising the following steps: S1, mixing calcium hydroxide powder with water and granulating once to obtain core particles; S2, mixing the core particles, calcium hydroxide and steel slag, performing secondary granulation, coating the surface of the core particles with a transition layer, and obtaining a first intermediate product; S3, repeating step S2, and gradually reducing the mass ratio of calcium hydroxide and steel slag in step S2, coating the surface of the core particles with multiple transition layers, and obtaining a second intermediate product; S4, mixing the second intermediate product, steel slag and water, and performing tertiary granulation, coating the surface of the second intermediate product with a shell layer, to obtain a third intermediate product; S5. subjecting the third intermediate product to accelerated carbonation curing to obtain carbonated steel slag artificial aggregate.
[0031] In some embodiments, the carbonation degree of calcium hydroxide powder in the inner core particles of the carbonated steel slag artificial aggregate is no more than 20%, and the splitting strength of the carbonated steel slag artificial aggregate is 4-6 MPa.
[0032] In some embodiments, the conditions for accelerating carbonation are: CO2 volume concentration of 20-99%, pressure of 0.1-0.3 MPa, and time of 8-24 h.
[0033] In some embodiments, the water-to-solid ratio of the inner core particles is 0.45-0.55.
[0034] In some embodiments, the water-to-solid ratio of the shell is 0.10-0.20.
[0035] In some embodiments, the calcium hydroxide powder has a particle size of less than 200 mesh.
[0036] In some embodiments, the slag has a particle size of less than 200 mesh.
[0037] In some embodiments, the diameter of the core particles is 1 / 3 to 1 / 2 of the diameter of the carbonated steel slag artificial aggregate.
[0038] A third aspect is the use of a carbonated steel slag artificial aggregate with self-repairing function in concrete.
[0039] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0040] 1. Preparation method Embodiment 1~6 The calcium hydroxide powder is subjected to rotary granulation to form core particles, and the water-solid ratio of the core particles is 0.45-0.55; the first transition layer is coated on the surface of the core particles by rotary granulation, and the mass ratio of calcium hydroxide to steel slag in the transition layer is (4-2):1; the second transition layer is coated on the first transition layer by rotary granulation, and the mass ratio of calcium hydroxide to steel slag in the transition layer is 1:(4-2); the steel slag powder shell is coated on the second transition layer by rotary granulation, and the water-solid ratio of the shell is 0.10-0.20. The particle size of calcium hydroxide powder and steel slag powder is less than 200 mesh; the diameter of the core particles is 1 / 3-1 / 2 of the diameter of carbonated steel slag artificial aggregate particles. Finally, the carbonated steel slag artificial aggregate is placed in a closed container with a CO2 concentration of 99% and a CO2 pressure of 0.2 MPa for accelerated carbonation reaction for 12 hours to obtain carbonated steel slag artificial aggregate.
[0041] The single particle splitting strength test of the aggregates prepared in Examples 1 to 6 was performed using formula (1). σ=2.8P / (πD 2 )(1) Wherein: σ is the splitting strength of artificial aggregate (MPa), D is the distance between the loading points (mm), and P is the splitting load (N). The reaction degree of calcium hydroxide was calculated by thermogravimetric method. The specific parameters and performance indicators of Examples 1 to 6 are shown in Table 1.
[0042] Table 1 Specific parameters and performance indicators of artificial aggregates prepared in Examples 1 to 6
[0043] It can be seen from Table 1 that the carbonation degree of the internal calcium hydroxide powder of the carbonated steel slag artificial aggregate prepared in Examples 1 to 6 of the present invention is no more than 20%, and the splitting strength of a single aggregate particle is 4 to 6 MPa.
[0044] Embodiments 7 to 12 The calcium hydroxide powder is made into core particles by rotary granulation, and the water-solid ratio of the core particles is 0.50; the first transition layer is coated on the surface of the core particles by rotary granulation, and the mass ratio of calcium hydroxide to steel slag in the transition layer is 3:1; the second transition layer is coated on the first transition layer by granulation, and the mass ratio of calcium hydroxide to steel slag in the transition layer is 1:3; the steel slag powder shell layer is coated on the second transition layer by granulation, and the water-solid ratio of the shell layer is 0.15. The particle size of calcium hydroxide powder and steel slag powder is less than 200 mesh; the diameter of the internal calcium hydroxide powder particle is 1 / 3 of the diameter of the carbonated steel slag artificial aggregate particle. Finally, the carbonated steel slag artificial aggregate is placed in a closed container with a CO2 concentration of 20~99% and a CO2 pressure of 0.1~0.3 MPa to accelerate the carbonation reaction for 8~24 hours to obtain carbonated steel slag artificial aggregate.
[0045] The single particle splitting strength test of the aggregates prepared in Examples 7 to 12 was carried out using formula (1), and the reaction degree of calcium hydroxide was calculated by thermogravimetry. The specific parameters and performance indicators of Examples 7 to 12 are shown in Table 2.
[0046] Table 2 Specific parameters and performance indicators of artificial aggregates prepared in Examples 7 to 12
[0047] It can be seen from Table 2 that the carbonation degree of the internal calcium hydroxide powder of the carbonated steel slag artificial aggregate prepared in Examples 7 to 12 of the present invention is no more than 20%, and the splitting strength of a single aggregate particle is 4-6 MPa.
[0048] Comparative Examples 1 to 4 The calcium hydroxide powder is made into core particles by rotary granulation; a transition layer is coated on the surface of the core particles by rotary granulation; a steel slag powder shell is coated on the transition layer by rotary granulation, and the outer layer water-solid ratio is 0.15. The particle size of the calcium hydroxide powder and the steel slag powder is less than 200 mesh; the diameter of the core particles is 1 / 3 of the diameter of the carbonated steel slag artificial aggregate particles. Finally, the carbonated steel slag artificial aggregate is placed in a closed container with a CO2 concentration of 99% and a CO2 pressure of 0.2MPa for accelerated carbonation reaction for 12 hours to obtain carbonated steel slag artificial aggregate.
[0049] The single particle splitting strength test of the carbonated steel slag artificial aggregate prepared in Comparative Examples 1 to 4 was carried out using formula (1), and the reaction degree of calcium hydroxide was calculated by thermogravimetric method. The specific parameters and performance indicators of Comparative Examples 1 to 4 are shown in Table 3.
[0050] Table 3 Specific parameters and performance indicators of carbonated steel slag artificial aggregates prepared in Comparative Examples 1 to 4
[0051] As shown in Table 3, in Comparative Example 1, when the water-solid ratio of the inner core calcium hydroxide is too low, the single particle splitting strength of the obtained carbonated steel slag artificial aggregate and the degree of reaction of the inner core particles are too high. When the concrete cracks, the internal repair substances cannot be released, and the excessive degree of reaction of the inner core particles will affect the self-repairing effect of the carbonated steel slag artificial aggregate. In Comparative Example 2, when the water-solid ratio of the inner core calcium hydroxide particles is too high, the single particle splitting strength of the obtained carbonated steel slag artificial aggregate and the degree of reaction of the inner core particles are too low, resulting in the carbonated steel slag artificial aggregate being extremely easy to break during the concrete mixing process.
[0052] As shown in Table 3, in Comparative Examples 3 and 4, when only one transition layer or no transition layer is provided, the obtained carbonated steel slag artificial aggregate cannot meet the technical requirements of the internal calcium hydroxide carbonation degree not exceeding 20% and the single particle aggregate splitting strength of 4-6MPa. The performance difference between the carbonated calcium hydroxide in the core particles and the carbonated steel slag in the shell is too large, and multiple transition layer treatments are used to reduce the gradient and reduce the influence of the carbonation reaction of the core on the carbonation reaction of the shell steel slag.
[0053] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A carbonated steel slag artificial aggregate with self-repairing function, characterized in that: It includes core particles, a plurality of transition layers and a shell layer from the inside to the outside, wherein the core particles are composed of carbonated calcium hydroxide, the shell layer is composed of carbonated steel slag, the plurality of transition layers are provided with at least two layers, and the mass ratio of calcium hydroxide to steel slag gradually decreases from the inside to the outside; The carbonation degree of calcium hydroxide in the inner core particles is not more than 20%, and the splitting strength of the carbonated steel slag artificial aggregate with self-repairing function is 4-6MPa.
2. The carbonated steel slag artificial aggregate with self-repairing function according to claim 1, characterized in that: The mass ratio of calcium hydroxide to steel slag in the transition layer close to the core particles is (4-2):1, and the mass ratio of calcium hydroxide to steel slag in the transition layer close to the shell layer is 1:(4-2).
3. The method for preparing a carbonated steel slag artificial aggregate with self-repairing function according to claim 1 or 2, characterized in that: The following steps are involved: S1, mixing calcium hydroxide powder with water and granulating once to obtain core particles; S2, mixing the core particles, calcium hydroxide and steel slag, performing secondary granulation, and coating the surface of the core particles with a transition layer to obtain a first intermediate product; S3, repeating step S2, and gradually reducing the mass ratio of calcium hydroxide and steel slag in step S2, coating the surface of the core particles with multiple transition layers to obtain a second intermediate product; S4, mixing the second intermediate product, steel slag and water, and performing granulation three times, coating the surface of the second intermediate product with a shell layer, to obtain a third intermediate product; S5. subjecting the third intermediate product to accelerated carbonation curing to obtain carbonated steel slag artificial aggregate.
4. The method for preparing a carbonated steel slag artificial aggregate with self-repairing function according to claim 3, characterized in that: The conditions for accelerating carbonation are: CO2 volume concentration of 20-99%, pressure of 0.1-0.3 MPa, and time of 8-24 hours.
5. The method for preparing carbonated steel slag artificial aggregate with self-repairing function according to claim 3, characterized in that: The water-to-solid ratio of the inner core particles is 0.45-0.
55.
6. The method for preparing carbonated steel slag artificial aggregate with self-repairing function according to claim 3, characterized in that: The water-to-solid ratio of the shell is 0.10-0.
20.
7. The method for preparing carbonated steel slag artificial aggregate with self-repairing function according to claim 3, characterized in that: The particle size of the calcium hydroxide powder is less than 200 meshes.
8. The method for preparing carbonated steel slag artificial aggregate with self-repairing function according to claim 3, characterized in that: The particle size of the steel slag is less than 200 meshes.
9. The method for preparing carbonated steel slag artificial aggregate with self-repairing function according to claim 3, characterized in that: The diameter of the core particles is 1 / 3 to 1 / 2 of the diameter of the carbonated steel slag artificial aggregate.
10. Use of the carbonated steel slag artificial aggregate with self-repairing function according to claim 1 or 2 in concrete.